KESIAPAN SISWA DAN GURU DALAM PEMBELAJARAN PASCA COVID-19 PADA KOMPETENSI KEAHLIAN TKRO SMK NEGERI 5 SURAKARTA - Irfan Al Islam; Zainal Arifin (Journal of Automotive Technology and Education, 2024)
This study aims to determine the readiness of students and teachers in the implementation of face-to-face (offline) learning in the TKRO Expertise Competency of SMK Negeri 5 Surakarta. This research is descriptive research. The subjects of this study were class X students and educators in the TKRO department of SMK Negeri 5 Surakarta carried out by purposive sampling sample method. Data collection is done by observation, interviews, and documentation. The analytical technique used is a qualitative analysis technique from Miles and Huberman. This study found that students are ready to carry out learning activities, this is based on the fulfillment of four aspects of indicators, namely knowledge readiness, physical readiness, mental readiness, and emotional readiness. Educators are also ready to carry out face-to-face learning, this is also based on the fulfillment of four aspects of indicators, namely: (1) knowledge, educators know and understand offline learning procedures, (2) physical, educators are able to carry out offline learning, (3) mental, educators do not experience difficulties in offline learning, (4) emotional, educators choose offline learning rather than online.